2023
DOI: 10.2147/jpr.s409658
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Radiofrequency Decreases pERK and Affects Intracellular Ca2+ Influx, Cytosolic ATP Level, and Mitochondrial Membrane Potential in the Sensitized Dorsal Root Ganglion Neuron Induced by N-Methyl D-Aspartate

Abstract: Background:The molecular mechanism of pulsed radiofrequency (PRF) in chronic pain management is not fully understood. Chronic pain involves the activation of specific N-Methyl D-Aspartate receptors (NMDAR) to induce central sensitization. This study aims to determine the effect of PRF on central sensitization biomarker phosphorylated extracellular signal-regulated kinase (pERK), Ca 2+ influx, cytosolic ATP level, and mitochondrial membrane potential (Δψm) of the sensitized dorsal root ganglion (DRG) neuron fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Our study found that 2Hz 20-millisecond pulsed radiofrequency for 600 seconds significantly decreased the pERK level compared to the control, indicating decreased sensitization. 2 This result shows the scientific evidence that pulsed radiofrequency could directly reduce one of the biological processes of pain generation. However, in clinical practice, the overall outcome of PRF is achieved at two weeks, one month, three months, or six months after the procedure.…”
Section: Dear Editormentioning
confidence: 56%
“…Our study found that 2Hz 20-millisecond pulsed radiofrequency for 600 seconds significantly decreased the pERK level compared to the control, indicating decreased sensitization. 2 This result shows the scientific evidence that pulsed radiofrequency could directly reduce one of the biological processes of pain generation. However, in clinical practice, the overall outcome of PRF is achieved at two weeks, one month, three months, or six months after the procedure.…”
Section: Dear Editormentioning
confidence: 56%
“…This study uses DRG neurons that are differentiated from F11 cell line (08062601; Sigma, USA). Cell culture method according to Hashemian et al 21 with modifications described in a previous study by Laksono et al 22 We use DRG neurons that differentiated from F11 cell line on day 5. In this study, there were three treatment groups with nine replicates in each group ( Figure 1 ), including the control, 2 Hz PRF, and 4 Hz groups.…”
Section: Methodsmentioning
confidence: 99%
“…PRF treatment was carried out by transmitting pulsed frequencies of 2 Hz and 20 ms for 360 s (2 Hz group) and 4 Hz and 10 ms for 360 s (4 Hz group). PRF treatment is based on Laksono et al 22 study. Both PRF frequencies delivered the same energy, following the formula derived from Ohm’s law:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation